Microbial community and metabolic characteristics evaluation in start-up stage of electro-enhanced SBR for aniline wastewater treatment. (February 2022) - Feng, Jiapeng; Zhang, Qian; Tan, Bin; Li, Meng; Peng, Haojin; He, Jing; Zhang, Yunjie; Su, Junhao
Abstract: An electro-enhanced sequencing batch reactor (E-SBR) was constructed to treat 400 mg/L aniline wastewater and realized system rapid start-up. The aniline degradation efficiency was almost 100% and the total nitrogen removal rate was 80% in the E-SBR. High-throughput sequencing showed that the microbial community in E-SBR changed greatly. At genus level, Anaerolineae, Rhodococcus, Luteococcus, Deniratisoma, and SM1A02 enriched in activated sludge. Thauera, Ellin6067, Arenimonas, Hydrogenophaga enriched in the electrode biofilm. These functional microorganisms accounted for a large proportion and played an important role in the removal of pollutants. Meanwhile, the microorganism metabolism in the E-SBR system was significantly different from that in the traditional SBR system, the E-SBR system had higher nitrogen metabolic and carbohydrate metabolism abundance to ensure the effective removal of aniline and nitrogen. Graphical abstract: Unlabelled Image Highlights: Electrical stimulation realized faster system startup in aniline wastewater treatment. Electrical stimulation led to higher aniline and nitrogen removal efficiency. Essential functional genera were enriched effectively in SBR by electrical stimulation. PICRUSt analysis showed enriched nitrogen and carbohydrate metabolism in system.